Cyanobacteria blooms in the Baltic Sea: a review of models and facts - B. Munkes; U. Löptien; U. Löptien; H. Dietze; H. Dietze (Biogeosciences, 2021)
The ecosystem of the Baltic Sea is endangered by eutrophication. This has triggered expensive international management efforts. Some of these efforts are impeded by natural processes such as nitrogen-fixing cyanobacteria blooms that add bioavailable nitrogen to the already over-fertilized system and thereby enhance primary production, export of organic matter to depth, and associated oxygen consumption. Controls of cyanobacteria blooms are not comprehensively understood, and this adds to the uncertainty of model-based projections into the warming future of the Baltic Sea. Here we review our current understanding of cyanobacteria bloom dynamics. We summarize published field studies and laboratory experiments and dissect the basic principles ingrained in state-of-the-art coupled ocean–circulation biogeochemical models.